Doctoral education in the UK (Brunel University experience) - T. Kalganova; Elvira E. Valeeva; Yulia N. Ziyatdinova; Irina G. Obukhova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The past decade has seen a number of fundamental changes that have affected the Russian higher education and doctoral education in particular. Currently, there is a large number of problems related to the content and structure of doctoral degree programs. The analysis and study of the UK experience in organizing doctoral education programs can be used to solve some of these problems. Brunel University is one of the most prominent UK universities with strong academic traditions aimed at training highly qualified researchers. The article describes the main types and contents of doctoral degree programs, supervision principles, educational and research activities of a PhD student and the procedures for the viva process at Brunel University. Through analyzing the Brunel University experience, the authors summarize the factors that contribute to the leading position of the university in the UK and EHEA and provide close links between industry, doctoral education and research.